Analysis of The Effect of Competence and Education and Training on Employee Performance Through Work Commitment as Intervening Variable (Study at the East Java Provincial Forestry Service) - Edi Yulianto; Abadi Sanosra; Toni Herlambang (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2022)
The purpose of this study was to determine directly or indirectly the effect of competence and education and training on employee performance through work commitment as an intervening variable at the East Java Provincial Forestry Service. This research is a quantitative research with a survey approach. By number of samples104 respondents. Testing the instrument using validity and reliability tests while the types of data used are primary and secondary data. The analysis technique used is the Structural Equation Model (SEM) using WarpPLS. The results of data analysis show that the employee competence variable is0, 927significant effect on work commitment of 0,900, Education and Training of 0, 931 significant effect on work commitment of 0,900, employee competence of 0, 927 significant effect on employee performance of 0, 934, education and training have a significant effect on employee performance, work commitment is 0,900 significant effect on employee performance of 0, 934.